Evaluasi Program Pelatihan Menjahit di LPK Anita Kota Serang - Ahmad Rifai; Ira Permata Sari; Nyimas Melati Juniar; Anastasia Vivi Iswandari; Zafirah Suci Ramadhani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Globalization is so fast causing changes in the field of education. So that non-formal institutions such as Courses and Training Institutions (LKP) must be prepared for this. The existence of LKP has a role in alleviating ignorance, unemployment, poverty and increasing one's skills so that LPK is increasingly being looked at by the public, one of which is LPK Anita. The purpose of establishing LPK Anita is to have the ability to be imparted to people who need this knowledge. This evaluation aims to determine the efficiency and effectiveness of the sewing training program at LPK Anita by using the CIPP evaluation model (Context, Input, Process and Product). The evaluation method used is interview. Sources of data come from primary data (administrators, LPK instructors and training participants) and secondary data (relevant literature and documentation). The evaluation instruments used are interview guides, observations, and documentation. The data analysis technique used is qualitative data analysis through data collection, reduction, data display and drawing conclusions. So, the evaluation results that have been carried out in the context evaluation at Anita's LPK are in sync with the needs and goals. Input evaluation consists of training media, training materials, learning resources, funding, facilities and infrastructure comparable to expected. Process evaluation includes instructor activity and participant activity running smoothly. Product evaluation includes program impact, output produced by participants and appropriate program benefits.